A look at the approach to corruption in Argentina - E. Oestmann, Germán (Seven Editora, 2023)
The objective of this work was to analyze the phenomenon of corruption and its consequences in democratic societies. Therefore, a search for information was carried out on its generalities and consequences. Corruption negatively affects the public purposes of the Social Constitutional State of Law, economically disturbing the heritage of a nation, as well as the well-being of society, which negatively affects the quality of life of its citizens, as well as their human rights, social and economic DOI: 10.56238/pacfdnsv1-006